Chinese medicine ulcer oil promotes the healing of diabetic foot ulcers. Issue 7 (July 2018) - Jia, Hui; Yang, Bohua; Li, Youshan; Liang, Chen; Lu, Haibin; Lin, Dongyang; Ju, Shang
Abstract: Objective: This study aimed to investigate the mechanism by which Chinese herbal medicine ulcer oil (UO) accelerates ulcer healing in a diabetic ulcer rat model. Methods: Sprague Dawley rats were allocated at random into four groups: a control group, a positive control group (PC), a UO treatment group and an ethacridine lactate solution treatment group. Subcutaneous tissue was surgically removed from the rats on days 3, 7 and 14. The levels of protein phosphotyrosine phosphatase 1B (PTP1B), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF) and advanced glycation end products (AGEs) were detected using western blot analysis. Results: PTP1B protein expression was significantly lower in the UO group compared with the PC group. VEGF protein expression was significantly higher in the UO group than in the control group on day 3. PDGF protein expression in the UO group was significantly higher than in the PC group on day 3. AGE expression was significantly lower in the UO group than in the PC group. Conclusions: UO may downregulate PTP1B and AGEs and upregulate VEGF and PDGF, which may contribute to the inhibition of the inflammatory response and promote the healing of diabetic foot ulcers.